2019
DOI: 10.1136/bmjopen-2019-029679
|View full text |Cite
|
Sign up to set email alerts
|

A bit or a lot on the side? Observational study of the energy content of starters, sides and desserts in major UK restaurant chains

Abstract: ObjectivesOur objective was to examine the kilocalorie (kcal) content of starters, sides and desserts served in major UK restaurant chains, comparing the kcal content of these dishes in fast-food and full-service restaurants.DesignObservational study.SettingMenu and nutritional information provided online by major UK restaurant chains.MethodDuring October to November 2018, we accessed websites of restaurant chains with 50 or more outlets in the UK. Menu items that constituted starters, sides or desserts were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Most of the QSR chains had high-energy chips/fries as the only available option as part of combination deals. This finding is in line with a 2019 study (35) conducted in the UK that highlighted the high energy content of the sides and desserts sold in QSR chains.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the QSR chains had high-energy chips/fries as the only available option as part of combination deals. This finding is in line with a 2019 study (35) conducted in the UK that highlighted the high energy content of the sides and desserts sold in QSR chains.…”
Section: Discussionsupporting
confidence: 89%
“…We recently found that 91% of main meals served in major UK restaurant chains contained more than 600 kcal—the energy content for a main meal recommended by Public Health England 4. Consistent evidence of easy availability of other food products (eg, beverages, desserts, side dishes) that are high in calories in the out-of-home sector has also been reported in the UK 56…”
Section: Excessively Calorific Mealsmentioning
confidence: 73%
“…They found 86% of popular menu items were discretionary foods and beverages (also known as junk food), which are defined as items high in added salt, saturated fat, sugar and low in fibre by the Australian Dietary Guidelines [ 10 , 13 ]. Previous studies have described the nutritional composition of meals from takeaway franchises (chain stores that prepare and sell meals/snacks ready for immediate consumption, offered in specialised packaging, e.g., McDonalds Âź , or KFC Âź ) that are subject to menu labelling [ 14 , 15 ]. However, independent takeaways (takeaway outlets that are not franchises, e.g., local kebab shop) [ 16 ], are not subject to this regulation and were reported to be the second largest (30%) food outlet type on OFD platforms after takeaway franchises [ 10 ].…”
Section: Introductionmentioning
confidence: 99%